Development of an ICT Infrastructure–Based Public Service Transparency Index for Public Accountability in Smart City Local Governments - Nurhimawan, Latif; Sari, Novita; Maharani, Augustin Dara Putri; Adelia, Vanya Putri; Faradanty, Az Zahwa Firstania Raizkha; Sabariah, Hany; Fahrina, Alisha Izzah; Wijaya, Chornelia Putri Indah; Aazam, Mohd (Journal of Strategic Behaviour Accounting, 2026)
The development of Smart City initiatives has intensified the use of information and communication technology (ICT) to enhance transparency in local government public services. Within the smart governance framework, official local government websites serve as key digital platforms for disseminating public service information. However, existing e-government evaluation frameworks primarily rely on macro-level indicators, providing limited assessment of service-level transparency. This study develops and applies an ICT infrastructure–based Public Service Transparency Index to evaluate transparency practices on local government websites in the Smart City context. Using quantitative content analysis, the study examines the official websites of 16 local governments implementing Smart City initiatives. Data were collected using 12 indicators organized into six transparency dimensions. The findings reveal substantial variation in transparency performance, with information-oriented dimensions generally achieving higher scores than operational access dimensions. These results indicate that transparency practices remain largely document-oriented and highlight the need to strengthen operational service accessibility. The proposed index offers a practical framework for assessing and improving public service transparency in Smart City implementation.